2013
DOI: 10.1186/2050-2974-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and distinctiveness of DSM-5 eating disorder diagnoses: findings from a large naturalistic clinical database

Abstract: BackgroundDSM-IV eating disorder (ED) diagnoses have been criticized for lack of clinical utility, diagnostic instability, and over-inclusiveness of the residual category “ED not otherwise specified” (EDNOS). Revisions made in DSM-5 attempt to generate a more scientifically valid and clinically relevant system of ED classification. The aim with the present study was to examine clinical characteristics and distinctiveness of the new DSM-5 ED diagnoses, especially concerning purging disorder (PD). MethodsUsing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 56 publications
(68 reference statements)
10
69
2
2
Order By: Relevance
“…Well validated and structured methods for diagnostics and self-rating were used. An attrition rate of 48% is potentially a threat to generalizability, yet attrition analyses found no significant differences, in concordance with another study on the database [45]. Patients in the current study received treatment of various modalities (e.g., medical, psychological, pedagogical, nutritional, social, physical), length and intensity (e.g., inpatient, day-patient, out-patient).…”
Section: Discussionsupporting
confidence: 78%
“…Well validated and structured methods for diagnostics and self-rating were used. An attrition rate of 48% is potentially a threat to generalizability, yet attrition analyses found no significant differences, in concordance with another study on the database [45]. Patients in the current study received treatment of various modalities (e.g., medical, psychological, pedagogical, nutritional, social, physical), length and intensity (e.g., inpatient, day-patient, out-patient).…”
Section: Discussionsupporting
confidence: 78%
“…BMI) that one might generally expect for the BED group [73]. Nevertheless, the variability of both current and agehistorical variables within BED population is well documented [73,74], and mean values of both dietary restraint and BMI for BED cases are quite close to those observed in other clinical studies [76,77], [73]. Since the mean age of our BED participants at the time of assessment is consistent with that reported in several Italian studies [76,78], but lower than that of American studies (ranging from 38 to 48 years) [73], the possibility that Italians with BED are less tolerant of their overweight condition [78,79] and thus seek treatment more often than their US counterparts should not be ruled out.…”
Section: Discussionsupporting
confidence: 67%
“…Although our results demonstrated that individuals with BED have a less severe (eating disorder) psychopathology (see Table ), this is not reflected in a better outcome. Given the fact that eating disorder classifications can be regarded as snapshots taken throughout the course of an illness, attention should be paid to delineating which symptoms are present and which are not, because of the general instability of eating disorder symptoms and diagnoses and their highly problematic operationalization …”
Section: Discussionmentioning
confidence: 99%